2007
DOI: 10.1177/0265532207080771
|View full text |Cite
|
Sign up to set email alerts
|

Construct implications of including still image or video in computer-based listening tests

Abstract: Over the past decade, listening comprehension tests have been converting to computer-based tests that include visual input. However, little research is available to suggest how test takers engage with different types of visuals on such tests. The present study compared a series of still images to video in academic computer-based tests to determine how test takers engage with these two test modes. The study, which employed observations, retrospective reports and interviews, used data from university-level non-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
118
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(133 citation statements)
references
References 25 publications
10
118
0
5
Order By: Relevance
“…For example, when learners fail to recognize the overall organization of the ideas in a text, they have discoursal problems. Gruba (1997) and Ockey (2007) maintain that focusing on rhetorical signaling cues can help listeners understand the discoursal features of the text they are listening to. For instance, a competent listener would recognize the cue, "Let me put it in another way!"…”
Section: Theory and Practice In Language Studiesmentioning
confidence: 99%
“…For example, when learners fail to recognize the overall organization of the ideas in a text, they have discoursal problems. Gruba (1997) and Ockey (2007) maintain that focusing on rhetorical signaling cues can help listeners understand the discoursal features of the text they are listening to. For instance, a competent listener would recognize the cue, "Let me put it in another way!"…”
Section: Theory and Practice In Language Studiesmentioning
confidence: 99%
“…Second, it is in harmony with common practice in the classroom (Buck, 2001;Gruba, 1997;PardoBallester, 2016). Third, it increases the validity of the test (Bejar, Douglas, Jamieson, Nissan, & Turner, 2000;Wagner, 2007Wagner, , 2008Wagner, , 2010a, its authenticity (Alderson, 2005;Bejar et al 2000;Ockey, 2007;Wagner, 2007Wagner, , 2008 and its naturalness (Alderson, 2005). Fourth, "seeing the situation and the participants tends to call up relevant schemes" (Buck, 2001, p. 172).…”
mentioning
confidence: 99%
“…Ockey (2007) found that students shown the minimum amount of engagement while taking the video listening test. On the other hand, investigated the test-takers' viewing rate and found that students showed 69% eye contact with the visual materials while taking the listening test.…”
Section: B Test-takers' Reactions Over Using Different Modalities Ofmentioning
confidence: 97%
“…Brett (1997) argued that students became busy reading the test books and neglected watching the visual materials. Coniam (2001) and Ockey (2007) believed that sidetracking and distraction are other factors that affect test-takers in this kind of test. According to Buck (2001), the ability to comprehend the language similar to those of the target language domain is different from the ability to understand "subtle visual information" (p. 172).…”
Section: B Test-takers' Reactions Over Using Different Modalities Ofmentioning
confidence: 99%
See 1 more Smart Citation